Does the Adoption of an In-Depth Questioning Approach Promote Self-Reflexivity? Its Application to the Social Work Education Context. - Damian Spiteri (Social Work and Society, 2013)
Enhanced self-reflexivity is seen as an essential aspect of social work practice. This paper explores whether students who engaged in practice-oriented training sessions (practice workshops) saw these seminars as giving them the self-insight necessary to carry out their placements with the requisite level of awareness. The paper will also appraise whether the students believed that these practice workshops enabled them to engage in in-depth questioning and how this influenced their thinking in relation to the interventions that they would be carrying out whilst on their placements.